The Correlation Between Smoking Habits and Stroke Severity Among Patient with Stroke at General Public Hospital in Bandung, Indonesia - Syaharani, Syarifa Sophia; Agustiyowati, Tri Hapsari Retno; Rohyadi, Yosep (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Stroke, a severe neurological condition, can be fatal and can be influenced by smoking habits and lifestyle choices, as it can cause plaque buildup in blood vessels. This study to determine the association between smoking behaviour and the severity of stroke in stroke patients. Methods: The study used cross-sectional research with 51 respondents, measuring smoking habits and stroke severity. Results showed a significant positive relationship between smoking habits and stroke severity, with 23.5% having light smoking and 33.3% having mild strokes. Results: The research reveals that 62.7% of stroke patients treated at Al Ihsan Regional Hospital are male, with most having infarction strokes and being over 60 years old. Most have a smoking habit of 10-20 cigarettes per day, with moderate habits. Smoking habits can trigger atherosclerosis, causing strokes and affecting clinical outcomes. Conclusions: The study found a moderate relationship between smoking habits and stroke severity in stroke patients at Al Ihsan Regional Hospital, with smoking habits affecting the degree of stroke and causing infarction.